The forgotten daughter : a novel - Goodman, Joanna, 1969- (Harper, an imprint of HarperCollinsPublishers, 2020)
In 1992, an assassin's daughter fights for Quebec's independence at the side of the man she loves, a separatist-opposing journalist whose sister, one of the Duplessis orphans--thousands of children falsely certified as mentally ill in the 1950s and 1960s by the provincial government--joins a reparations coalition.